Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.jstrokecerebrovasdis.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for the Classification of Etiologies of Neurologic Deterioration after Acute Ischemic Stroke

Abstract: Background Neurologic deterioration (ND) occurs in one third of patients with ischemic stroke and contributes to morbidity and mortality in these patients. Etiologies of ND and clinical outcome according to ND etiology are incompletely understood. Methods We conducted a retrospective investigation of all patients with ischemic stroke admitted to our center (July 2008 to December 2010), who were known to be last seen normal less than 48 hours before arrival. First-time episodes of ND during hospitalization we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 24 publications
(30 reference statements)
0
34
1
Order By: Relevance
“…[8,9] The frequency of neurological deterioration in this singlecenter study was 15.4%, which was higher than that of a retrospective study which assessed deteriorations within the first two days [10] and lower than those of two prospective studies (35% and 37%, respectively). [11,12] The studies for early neurological deterioration in non- thrombolyzed patients were found to have frequencies between 13 to 37% [13][14][15][16][17] Our patients with neurological progression had worse NIHSS scores on discharge, compared to non-progressive patients (8 vs 3.7), while the NIHSS scores were not different on admission between these two groups. These findings are consistent with previous reports.…”
Section: Discussionmentioning
confidence: 90%
“…[8,9] The frequency of neurological deterioration in this singlecenter study was 15.4%, which was higher than that of a retrospective study which assessed deteriorations within the first two days [10] and lower than those of two prospective studies (35% and 37%, respectively). [11,12] The studies for early neurological deterioration in non- thrombolyzed patients were found to have frequencies between 13 to 37% [13][14][15][16][17] Our patients with neurological progression had worse NIHSS scores on discharge, compared to non-progressive patients (8 vs 3.7), while the NIHSS scores were not different on admission between these two groups. These findings are consistent with previous reports.…”
Section: Discussionmentioning
confidence: 90%
“…ND was defined as an increase of 2 or more points on a patient's NIHSS within a 24-hour period, as previously described since this threshold has been associated with several poor outcome measures including discharge disability and death. 3 We used previously described etiologies as defined by Siegler et al 21 Patients with ND secondary to progressive stroke, new stroke, or intracerebral hemorrhage were classified as having nonreversible ND due to the fact that these etiologies may produce or extend any areas of ischemic neurologic injury from temporary or permanent impairment in cerebral perfusion (in keeping with our prior definitions). 6,21 Patients with ND secondary to edema, fluctuation in symptoms, seizure, extubation, sedation, or any hemodynamic, toxic, metabolic, or infectious etiology were classified as having a reversible cause of ND.…”
Section: Variable Selection and Definitionmentioning
confidence: 99%
“…3 We used previously described etiologies as defined by Siegler et al 21 Patients with ND secondary to progressive stroke, new stroke, or intracerebral hemorrhage were classified as having nonreversible ND due to the fact that these etiologies may produce or extend any areas of ischemic neurologic injury from temporary or permanent impairment in cerebral perfusion (in keeping with our prior definitions). 6,21 Patients with ND secondary to edema, fluctuation in symptoms, seizure, extubation, sedation, or any hemodynamic, toxic, metabolic, or infectious etiology were classified as having a reversible cause of ND. 21 Several etiologies of clinical deterioration after stroke have been previously investigated, 2,22,23 but this does not encompass all potential causes of ND.…”
Section: Variable Selection and Definitionmentioning
confidence: 99%
See 2 more Smart Citations